インドヨウ ナンキョクカイ オヨビ タイセイヨウ ナンキョクカイ ノ カイキョウ ニツイテ - 石野, 誠; イシノ, マコト; 奈須, 敬二; ナス, ケイジ; 小竹, 勇; コタケ, イサム; 田口, 武; タグチ, タケシ; 植松, 貞行; ウエマツ, サダユキ; 河嶌, 拓治; カワシマ, タクジ; et al. (国立極地研究所, 1963)
P(論文) Based on the data obtained by the UMITAKA-MARU (Tokyo Univ. of Fisheries, 1453) during the period from Dec. 1961 to Feb. 1962, the general oceanographic conditions are discussed in this paper. During this expedition the temperature, salinity, dissolved oxygen, PH, Phosphate-P and Silicate-Si are investigated at all stations. As a result the followings are summarized; (1) along the oceanographic sections off Australia and Africa the Antarctic Convergences are clearly distinguished, (2) in the Indian Antarctic waters the south-going warm deep water affects to the higher latitudes zone than in the Atlantic region, (3) in the Weddell cold water region where the northerly and southerly oceanographic sections are investigated the upwelling of Warm Deep Water is critically observed, (4) by the chart of dynamical topography the meandering of west-wind drift current around the Weddell cold water region is estimated. departmental bulletin paper